Emergency Department Utilization Patterns in Patients with Opioid-Related Emergency Department Visits. (12th May 2022) - Shastry, Siri; Counts, Christopher; Shegog, Evan; Loo, George; Cowan, Ethan
Abstract: Background: : Opioid-related Emergency Department (ED) visits have surged over the past decade. There is limited data on ED utilization patterns of patients with opioid use disorder (OUD). An improved understanding of utilization may underscore missed opportunities for screening, intervention and referral. Methods: : This was a retrospective 2:1 matched case-control study conducted at a single urban ED. Cases were patients with an opioid-related index ED visit from June 1, 2017 to May 31, 2018. Controls were patients with a non-opioid related index ED visit from June 1, 2018 to May 31, 2019. The primary outcome was the association between the number of ED visits in the 24-month period surrounding the index visit (12 months prior and 12 months following) and having an opioid-related index ED visit. Results: : There were a total of 224 cases. One or more visits preceding (OR: 1.63, 95% CI: 1.17, 2.26) and following the index visit (OR: 2.69, 95% CI: 1.91, 3.78) was significantly associated with case status. Following adjustment, a higher number of visits preceding (aOR: 1.24, 95% CI: 1.08, 1.43) and following the index visit (aOR: 1.39, 95% CI: 1.23, 1.57) remained significantly associated with case status. Conclusion: : Patients with an opioid-related index ED visit had significantly higher rates of ED utilization 12 months before and after the index visit when compared to a matched control population. These findings suggest that there are significant opportunities for ED intervention and referral to treatment both prior to and following an opioid-related ED visit in this patient population.